UI/UX Design of Waste Management Application Using Design Thinking Method - Regar Chairul Soleh; M Maukar (LPPM STIKOM Tunas Bangsa, 2024)
Effective and sustainable waste management is a global challenge that requires innovative solutions. This study proposes optimizing waste management through UI/UX design approach using the design thinking method. The stages of Empathize, Define, Ideate, Prototype, and Testing are employed to design the